2014
DOI: 10.3390/cancers6042356
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Intensity-Modulated Radiation Therapy (IMRT), Proton and 3D Conformal Radiotherapy (3D-CRT) for Reducing Perioperative Cardiopulmonary Complications in Esophageal Cancer Patients

Abstract: Background. While neoadjuvant concurrent chemoradiotherapy has improved outcomes for esophageal cancer patients, surgical complication rates remain high. The most frequent perioperative complications after trimodality therapy were cardiopulmonary in nature. The radiation modality utilized can be a strong mitigating factor of perioperative complications given the location of the esophagus and its proximity to the heart and lungs. The purpose of this study is to make a dosimetric comparison of Intensity-Modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 37 publications
4
52
1
Order By: Relevance
“…Another key finding of this study relates to the observed reduction in postoperative cardiovascular events among patients receiving IMRT. Research evaluating radiation dosimetry demonstrates that the more conformal radiation dose distributions with IMRT have the potential to reduce radiation doses to the heart compared to conventional forms of radiation 14,[25][26][27][28] . Similarly, other retrospective analyses have found potential reductions in cardiovascular toxicity associated with IMRT compared to older radiation techniques 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Another key finding of this study relates to the observed reduction in postoperative cardiovascular events among patients receiving IMRT. Research evaluating radiation dosimetry demonstrates that the more conformal radiation dose distributions with IMRT have the potential to reduce radiation doses to the heart compared to conventional forms of radiation 14,[25][26][27][28] . Similarly, other retrospective analyses have found potential reductions in cardiovascular toxicity associated with IMRT compared to older radiation techniques 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…The dosimetric advantages of proton therapy for esophageal cancer have been demonstrated in comparison to 3D-CRT and IMRT in several planning studies. [109][110][111] As compared to IMRT, both the two-beam and three-beam proton therapies resulted in much better lung sparing, with median lung V5, V10, V20, and MLD reduced by 35.6%, 20.5%, 5.8%, and 5.1 Gy and 17.4%, 8.4%, 5%, and 2.9 Gy, respectively. 110 In a dosimetric comparative study between IMRT and intensity-modulated proton therapy (IMPT), IMPT spared much more of the heart, lung, liver, and spinal cord.…”
Section: Further Dosimetric and Clinical Advantages: Proton Therapy Vmentioning
confidence: 99%
“…112 In another comparative planning study, proton plans showed a decreased dose to various volumes of the heart and lungs, especially lung V5, while achieving adequate target coverage when compared to both the IMRT and 3D-CRT plans. 109 Furthermore, proton therapy can also improve heart sparing in terms of heart V30 and mean heart dose, which may reduce the risk of radiation-induced cardiovascular toxicity. Ling et al 109 reported that the proton plans delivered a significantly lower dose to the left anterior descending artery and left ventricle in comparison to both the IMRT and 3D-CRT plans.…”
Section: Further Dosimetric and Clinical Advantages: Proton Therapy Vmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize potential radiation toxicity, small practical considerations such as how to use these wedge filters in treatment planning and modeling of these wedges in treatment planning beam profiles are very useful. The use of wedge filters in treatment of breast, thoracic, and pelvic tumors are very common and the steep dose gradient may produce hot spots in lungs, heart, and rectum in these cases [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%